Implementasi Jaringan IPv6 dan Constrained Application Protocol (CoAP) pada Sistem Monitoring Kualitas Air - Muhammad Wingga Woggiasworo; Sabriansyah Rizqika Akbar; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The development of IoT in smart device network protocols that generally enable internet protocols. IPv6 will be able to communicate with smart devices because the address space is quite large. Limited networks 6LoWPAN has characteristics for unstable networks with low bit-rates, and low costs. Reflecting on the problem of water quality monitoring needs, the implementation of sensor-nodes based on 6LoWPAN and CoAP is expected to be able to overcome these problems. Protocol CoAP is a medium as web messages transfer protocol for limited environments (eg: low-power and unstable networks). Accuracy temperature sensors DS18B20 is 95.9%. The average accuracy of 91.61% for the pH sensor. And the photodiode sensor with a value range of 1% -20% for clear and 80% -100% value range for murky which is used to detect turbidity levels. 6LoWPAN network and CoAP protocol can minimize shipping errors because it provides protocol resources. Average delay and packet loss 6LoWPAN network based on packet size of 56 bytes and 128 bytes is 13.4 ms and 20.1 ms with packet loss rate is 0% and 0% in distance of 5 meters. For the farthest distance of 40 meters, average delay is 30.8 ms and 39.7 ms with packet loss rate is 31%; 57% based on packet size 56 bytes and 128 bytes. Message delivery performance between nodes based on 6LoWPAN and CoAP gets a delivery time of 13.417 seconds for the distance 45 meters and 1.331 seconds for the distance of 5 meters.